A method for estimating the origin time of an ensuing mainshock by observations of preshock crustal seismic deformation - PAPAZACHOS, B. C.; KARAKAISIS, G. F.; PAPAZACHOS, C. B.; SCORDILIS, E. M.; SAVVAIDIS, A. S. (Bulletin of the Geological Society of Greece, 2001)
Observations on accelerating crustal deformation due to the generation of intermediate magnitude preshocks in the Aegean area are used to propose a method for prediction of the origin time of an ensuing mainshock. The method is based on a precursory seismic excitation that occurs in the preshock region at a time correlated to the origin time of the oncoming mainshock. The uncertainty in this prediction is of the order of ± 1.5 years with relatively high confidence ('90%).